Super-hydrophobic high-impermeability cement-based protection system and preparation method thereof

Through multi-layer protection systems, including permeable crystallization, cement-based protective materials and silane impregnation technology, the problem of degradation in traditional single protective materials is solved, significantly improving the durability and protective effect of concrete, extending service life and reducing maintenance costs.

CN119613151AInactive Publication Date: 2025-03-14盐城市港航事业发展中心 +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411863029.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The performance of traditional single protective materials decreases after long-term use, resulting in weakening of the durability and protective effect of concrete structures, increasing the frequency and cost of maintenance and replacement.

Method used

A multi-layer protection system is adopted, including permeable crystalline surface anti-seepage technology, high-performance cement-based protective material surface repair technology, and silane-impregnated surface superhydrophobic modification technology, to enhance the anti-seepage, freeze-thaw and carbonization properties of concrete.

Benefits of technology

Through the multi-layer protection system, the durability of cement-based materials is significantly improved, the service life of protective materials is extended, the cost of maintenance and replacement is reduced, and the overall performance of the structure is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613151A_ABST
    Figure CN119613151A_ABST
Patent Text Reader

Abstract

The invention discloses a super-hydrophobic high-impermeability cement-based protection system and a preparation method thereof.The preparation method comprises the steps that firstly, existing concrete is pretreated, then the surface of the concrete is densified through capillary crystallization, the internal structure of the concrete is repaired to a certain degree, and the concrete serves as first protection; secondly, on the basis, a high-performance cement-based material is adopted for conducting secondary protection on the concrete structure, and therefore the strength and durability of the concrete structure are improved; finally, active silicon-oxygen bonds in the molecular structure and hydration products of the cement-based material are subjected to a chemical reaction in a silane impregnation mode, stable silane polymers are formed to fill and seal pores in the cement-based material, and the super-hydrophobicity of the high-performance cement-based material is achieved; therefore, various durability such as permeation resistance, freezing and thawing resistance, carbonization resistance and the like of the cement-based material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of concrete protection, and specifically relates to a super-hydrophobic and highly impermeable cement-based protection system and a preparation method thereof. Background Art

[0002] As one of the most common building materials, concrete is widely used in various projects. When it is in a long-term complex immersion environment, it may cause internal erosion and dissolution, greatly reducing the strength and durability of the concrete, and eventually causing structural damage. Therefore, strengthening the corrosion resistance of concrete has become an effective way to increase the service life of building structures.

[0003] Traditional methods of improving the durability of concrete mostly use a single protective material. Although this method can improve durability, it also has some limitations. These materials may be able to significantly improve the durability of concrete in the initial stage, but over time, their performance tends to gradually decline, resulting in a weakened protective effect, requiring more frequent maintenance and replacement. The service life of protective materials is greatly shortened during long-term service, which increases the cost of protection while also increasing the difficulty of protection. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to solve the above-mentioned technical problems and to provide a super-hydrophobic and highly impermeable cement-based protective system and a preparation method thereof, which adopts multi-layer protection of penetration crystallization surface impermeability technology, high-performance cement-based protective material surface repair technology and silane impregnation surface super-hydrophobic modification technology to improve the various durability properties of cement-based materials such as anti-penetration, anti-freeze and thaw, and anti-carbonization.

[0005] Technical solution: The super-hydrophobic and high-permeability cement-based protective system described in the present invention includes a penetrating crystalline coating, a high-performance cement-based protective coating and a silane impregnated coating.

[0006] Preferably, the components and contents of the infiltration crystallization coating are calculated by weight percentage: 1-3wt% of inorganic silicon material, 1-3wt% of complex catalyst, 1-3wt% of water retention enhancer, 1-3wt% of polycarboxylate water reducer, and 80-90wt% of water.

[0007] Preferably, the inorganic silicon material is one or both of sodium silicate and potassium silicate.

[0008] Preferably, the complex catalyst is one or both of ethylenediaminetetraacetic acid and ethylenediaminetrimethylphosphonate, and the water retention enhancer is magnesium fluorosilicate.

[0009] Preferably, the components and contents of the high-performance cement-based protective coating are as follows, in percentage by weight: Portland cement 46-53 Silica Fume 19-25 Fly ash 9-14 Quartz sand 2-3 Carbon Fiber 0.3-0.9 Polypropylene fiber 0.1-0.3 Water reducing agent 2.8-6 Mixing water 7-17 Preferably, the components and contents of the silica fume, in weight percentage, are as follows: SiO2 solid content 90-95wt%, Al2O3 solid content 0.1-0.3 wt%, Fe2O3 solid content 0.1-0.4wt%, CaO solid content 0.5-1.2wt%, and MgO solid content 0.2-0.5wt%.

[0010] Preferably, the components and contents of the fly ash, in percentage by weight, are: SiO2 solid content 30-35wt%, Al2O3 solid content 10-14 wt%, Fe2O3 solid content 2-4wt%, CaO solid content 35-42wt%, and MgO solid content 5-7wt%.

[0011] Preferably, the main component of the quartz sand, SiO2, has a solid content of 90-99wt%, and Fe2O3 has a solid content of 0.02-0.06wt%.

[0012] Preferably, the silane impregnation coating is a silane impregnating agent, and preferably, the silane impregnating agent is isobutyltriethoxysilane.

[0013] The present invention also provides an application of a super-hydrophobic high-impermeability cement-based protective system in concrete protection, which is characterized by comprising the following steps: 1) Pre-treat the existing concrete surface. The surface to be treated should be dry, the surface temperature should be around 35°C, and there should be no dirt, oil stains, grease or other debris that reduces adhesion on the surface; 2) Apply the penetrating crystallization material to the existing concrete surface by brushing or spraying, repeat brushing or spraying 2-3 times, and keep the surface wet for 30-40 minutes to allow the material to penetrate completely. When brushing or spraying, the liquid should completely cover the surface; 3) Application of existing concrete surface coated with penetrating crystallization material: The mixed high-performance cement-based protective coating must be applied within 2.5-3 hours, and the thickness of the high-performance cement-based protective material is controlled at 5-10 mm; 4) Before silane impregnation, the surface of the ultra-high performance cement-based material should be cleaned of dust and oil. The surface of the ultra-high performance cement-based material should be dry before spraying silane, and construction can be carried out without free water on the surface.

[0014] 5) The construction of impregnated silane can be done by brushing, low-pressure spraying or rolling. The surface temperature of the ultra-high performance cement-based material should be between 5-45°C, and the spraying amount per coat should be 200-300ml / m 2 , spray twice.

[0015] Beneficial effects: "Nano glue" - an inorganic water-based penetrating crystalline material with sodium silicate and potassium silicate as the main components, is a concrete protection, repair and maintenance material that is different from traditional skin-type waterproof materials. It can penetrate into the interior of the concrete and provide long-lasting protection and repair. High-performance cement-based protective materials are a new type of cement-based material with excellent mechanical properties and durability. Through surface protection technology, ultra-high-performance cement-based protective materials are used as a protective layer for ordinary concrete structures, which can reduce the erosion and damage of external corrosive ions to concrete, and is beneficial to improving the durability of the concrete matrix. The principle of silane impregnating agents is mainly that their molecular structure contains active silicon-oxygen bonds, which can react chemically with the hydration products in the concrete substrate to form stable silane polymers, which can fill and seal the pores in the concrete, thereby improving the surface properties and durability of the concrete.

[0016] The present invention first pre-treats the existing concrete, and then densifies the concrete surface through penetration crystallization and repairs the internal structure of the concrete to a certain extent, which serves as the first layer of protection; secondly, on this basis, high-performance cement-based materials are used to provide secondary protection for the concrete structure, thereby improving the strength and durability of the concrete structure; finally, silane impregnation is used to allow the active silicon-oxygen bonds in its molecular structure to react chemically with the hydration products of the cement-based material to form a stable silane polymer that fills and seals the pores in the cement-based material, thereby achieving super-hydrophobicity of the high-performance cement-based material, thereby improving the various durability properties of the cement-based material, such as anti-penetration, anti-freezing and anti-thawing, and anti-carbonization. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a CT image of concrete surface treated by penetration crystallization according to the present invention.

[0018] Figure 2 This is a scanning electron microscope image of the infiltrated crystallization material layer after treatment in Example 1.

[0019] Figure 3 This is a scanning electron microscope image of the infiltrated crystallization material layer after treatment in Example 2.

[0020] Figure 4 This is the contact angle test of the concrete surface after the process treatment of Example 6.

[0021] Figure 5 This is the contact angle test of the concrete surface after the process treatment of Example 7.

[0022] Figure 6 This is the contact angle test of the concrete surface after the process treatment of Example 8. DETAILED DESCRIPTION

[0023] In order to deepen the understanding of the present invention, the present invention will be further described in detail below in conjunction with embodiments and drawings. The embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention.

[0024] Example 1 Composition of the infiltration crystal coating Sodium silicate 2.5wt%, complex catalyst-ethylenediaminetetraacetic acid 2wt%, water retention enhancer-magnesium fluorosilicate 2.5wt%, polycarboxylic acid water reducer (a mixture of acrylic acid, methacrylic acid and maleic anhydride, purchased from Guangdong Xinqi New Building Materials Co., Ltd., 5643513, the same below) 3wt%, water 90wt%.

[0025] Example 2 Composition of the infiltration crystal coating Potassium silicate 2.6wt%, complex catalyst-ethylenediaminetetraacetic acid 1.8wt%, water retention enhancer-magnesium fluorosilicate 2.7wt%, polycarboxylic acid water reducer 3.2wt%, water 89.7wt%.

[0026] Example 3 Preparation of high performance cement-based protective coating First, 49 wt% of silicate cement, 20.2 wt% of silica fume, 10.8 wt% of fly ash, 2.3 wt% of quartz sand and 3.2 wt% of water reducer (a mixture of acrylic acid, methacrylic acid and maleic anhydride, purchased from Guangdong Xinqi New Building Materials Co., Ltd., 5643513, the same below) were poured into a mixer and slowly stirred for 5 min to mix evenly; then, 0.3 wt% of carbon fiber and 0.1 wt% of polypropylene fiber were poured into the mixer and stirred for 5 min, and the total amount of mixing water used was 14.1 wt%.

[0027] Example 4 Preparation of high performance cement-based protective coating First, 50.1wt% of silicate cement, 21.8wt% of silica fume, 11.2wt% of fly ash, 2.28wt% of quartz sand and 2.9wt% of water reducer were poured into a mixer and slowly stirred for 5 minutes to mix evenly; then, 0.6wt% of carbon fiber and 0.2wt% of polypropylene fiber were poured into the mixer and stirred for 5 minutes, and the total amount of mixing water used was 10.92wt%.

[0028] Example 5 Preparation of high performance cement-based protective coating First, 51.5 wt% of silicate cement, 22.2 wt% of silica fume, 12.1 wt% of fly ash, 2.3 wt% of quartz sand and 2.96 wt% of water reducer were poured into a mixer and slowly stirred for 5 min to mix evenly; then, 0.9 wt% of carbon fiber and 0.2 wt% of polypropylene fiber were poured into the mixer and stirred for 5 min, and the total amount of mixing water used was 7.84 wt%.

[0029] Example 6 Construction process of super-hydrophobic high-permeability cement-based protective system 1) Pre-treat the existing concrete surface. The surface to be treated should be dry, the surface temperature should be between 5℃ and 35℃, and there should be no dirt, oil stains, grease or other debris that reduces adhesion on the surface; 2) Apply the penetrating crystallization material (Example 1) to the existing concrete surface by brushing or spraying, repeat brushing or spraying 2-3 times, and keep the surface wet for 30-40 minutes to allow the material to completely penetrate into the concrete; when brushing or spraying, the liquid should completely cover the surface; 3) Applying the existing concrete surface coated with the infiltrated crystallization material: The mixed high-performance cement-based protective coating (Example 3) needs to be applied within 2.5-3h, and the thickness of the high-performance cement-based protective material is controlled at 5-10 mm; 4) Before silane impregnation, the surface of the ultra-high performance cement-based material should be cleaned of dust and oil. The surface of the ultra-high performance cement-based material should be dry before spraying silane, and construction can be carried out without free water on the surface.

[0030] 5) The construction of impregnated silane can be done by brushing, low-pressure spraying or rolling. The surface temperature of the ultra-high performance cement-based material should be between 5-45°C, and the spraying amount per coat should be 200-300ml / m 2 , spray twice.

[0031] Example 7 Construction process of super-hydrophobic high-permeability cement-based protection system The construction process of this embodiment is consistent with that of Embodiment 6, except that the permeable crystallization material layer is selected from Embodiment 2, and the high-performance cement-based protective coating is selected from Embodiment 4.

[0032] Example 8 Construction process of super-hydrophobic high-permeability cement-based protective system The construction process of this embodiment is consistent with that of Embodiment 6, except that the permeable crystallization material layer is selected from Embodiment 1, and the high-performance cement-based protective coating is selected from Embodiment 5.

[0033] like Figure 1 As shown, Figure 1 is a CT image of concrete after being processed by the process of Example 6 of the present invention, Figure 1 -A is the concrete surface map, Figure 1 -B is a cross-sectional view of concrete, from Figure 1 -B, it can be seen that the darker color in the middle is concrete, and the lighter color of the outer circle is the protective material of the present invention.

[0034] Figure 2 , Figure 3They correspond to the scanning electron microscope images of Example 1 and Example 2 after the infiltration crystallization material layer treatment. It can be seen from the figure that the existing concrete surface treated with infiltration crystallization has obvious needle-like crystals, which are cross-linked and overlapped to form a dense and stable structure. The flocculent crystals should be calcium silicate crystals produced by silicone and unhydrated cement particles in the cracks, which improve the densification of the concrete surface.

[0035] like Figure 4-6 As shown, the contact angle test of the concrete surface after the process treatment of Examples 6, 7 and 8 respectively corresponds to the experimental data after the process treatment of Example 6: the strength of the high-performance cement-based protective material is 48.18 MPa, and after silane impregnation, the average contact angle between the high-performance cement-based material and water is 95; the experimental data after the process treatment of Example 7: the strength of the high-performance cement-based protective material is 56.27 MPa, and after silane impregnation, the average contact angle between the high-performance cement-based material and water is 96.42; the experimental data after the process treatment of Example 8: the strength of the high-performance cement-based protective material is 60.63 MPa, and after silane impregnation, the average contact angle between the high-performance cement-based material and water is 97.83. It can be seen that silane impregnation as the third layer of protection realizes the super-hydrophobic performance of the system.

[0036] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A super-hydrophobic and highly impermeable cement-based protective system, characterized in that: Including penetrating crystalline coatings, high-performance cement-based protective coatings and silane impregnated coatings.

2. The super-hydrophobic high-permeability cement-based protective system according to claim 1, characterized in that: The components and contents of the infiltration crystallization coating are calculated by weight percentage: 1-3wt% of inorganic silicon material, 1-3wt% of complex catalyst, 1-3wt% of water retention enhancer, 1-3wt% of polycarboxylic acid water reducer, and 80-90wt% of water.

3. The super-hydrophobic high-permeability cement-based protective system according to claim 2, characterized in that: The inorganic silicon material is one or both of sodium silicate and potassium silicate.

4. The super-hydrophobic high-permeability cement-based protective system according to claim 2, characterized in that: The complex catalyst is one or both of ethylenediaminetetraacetic acid and ethylenediaminetrimethylphosphonate, and the water retention enhancer is magnesium fluorosilicate.

5. The super-hydrophobic high-permeability cement-based protective system according to claim 1, characterized in that: The components and contents of the high-performance cement-based protective coating are calculated by weight percentage: 。 6. The super-hydrophobic high-permeability cement-based protective system according to claim 5, characterized in that: The components and contents of the silica fume are calculated by weight percentage: SiO2 solid content 90-95wt%, Al2O3 solid content 0.1-0.3wt%, Fe2O3 solid content 0.1-0.4wt%, CaO solid content 0.5-1.2wt%, and MgO solid content 0.2-0.5wt%.

7. The super-hydrophobic high-permeability cement-based protective system according to claim 5, characterized in that: The components and contents of the fly ash are calculated by weight percentage: SiO2 solid content 30-35wt%, Al2O3 solid content 10-14wt%, Fe2O3 solid content 2-4wt%, CaO solid content 35-42wt%, and MgO solid content 5-7wt%.

8. The super-hydrophobic high-permeability cement-based protective system according to claim 5, characterized in that: The main components of the quartz sand include SiO2 with a solid content of 90-99wt% and Fe2O3 with a solid content of 0.02-0.06wt%.

9. The super-hydrophobic high-permeability cement-based protective system according to claim 1, characterized in that: The silane impregnation coating is a silane impregnating agent, and preferably, the silane impregnating agent is isobutyltriethoxysilane.

10. Application of the super-hydrophobic high-permeability cement-based protective system as claimed in claims 1 to 9 in concrete protection, characterized in that: The steps include: 1) Pre-treat the existing concrete surface. The surface to be treated should be dry, the surface temperature should be around 35°C, and there should be no dirt, oil stains, grease or other debris that reduces adhesion on the surface; 2) Apply the penetrating crystallization material to the existing concrete surface by brushing or spraying, repeat brushing or spraying 2-3 times, and keep the surface wet for 30-40 minutes to allow the material to penetrate completely. When brushing or spraying, the liquid should completely cover the surface; 3) Application of existing concrete surface coated with penetrating crystallization material: The mixed high-performance cement-based protective coating must be applied within 2.5-3 hours, and the thickness of the high-performance cement-based protective material is controlled at 5-10 mm; 4) Before silane impregnation, remove dust and oil from the surface of the ultra-high performance cement-based material. Before spraying silane, the surface of the ultra-high performance cement-based material should be in a dry state, and construction can be carried out without free water on the surface; 5) The construction of impregnated silane can be done by brushing, low-pressure spraying or rolling. The surface temperature of the ultra-high performance cement-based material should be between 5-45°C, and the spraying amount per coat should be 200-300ml / m 2 , spray twice.

Citation Information

Patent Citations

  • Cement-based capillary crystalline waterproof material

    CN112794684A

  • Concrete surface anti-seepage hydrophobization construction method and anti-seepage hydrophobic structure

    CN113336573A

  • Water-based capillary crystalline waterproof agent and preparation method thereof

    CN117229084A

  • Ultra-high-performance cement-based protective material capable of conveniently identifying carbonization degree and preparation method of ultra-high-performance cement-based protective material

    CN118771824A

  • Method for improving durability of concrete

    JP2006036586A